Determinants of Innovation Capability in Libraries in Buleleng - N P. Pramita Utami; Komang Krisna Heryanda; M. Rudi Irwansyah (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
The rapid development of information technology has required libraries to enhance their innovation capability in order to remain relevant as agents of change in the digital era; however, empirical evidence in Buleleng Regency indicates that innovation among librarians remains relatively low despite existing organizational practices. Therefore, this study aims to analyze the influence of transformational leadership, knowledge sharing, and perceived organizational support on innovation capability. This research employs a quantitative approach based on the positivist paradigm with an explanatory design. Data were collected through questionnaires distributed to 60 librarians selected using proportional random sampling from a population of 71, and analyzed using multiple linear regression with SPSS, including validity, reliability, and classical assumption tests. The findings reveal that transformational leadership, knowledge sharing, and perceived organizational support each have a positive and significant effect on innovation capability, with knowledge sharing identified as the most dominant variable. Simultaneously, these variables explain 57.9% of the variance in innovation capability. In conclusion, innovation capability is influenced by the synergy of leadership, knowledge sharing, and organizational support, implying that libraries should strengthen these aspects to foster sustainable innovation.